Leukocytosis as Prediction for Early and Late Complications in Patient with St Segment Elevation Myocardial Infarction - Radhi Farhod Shlash1, Ahmed Diab Raheem2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: AMI ( acute myocardial infarction ) is one of the most common cause of death . In this study the prognostic value of WBC count in patient with AMI was assessed in 24 hrs after admission.STEMI (ST segment elevation myocardial infarction) is frequently associated with leukocytosis, it is that the peripheral leukocyte count have important prognostic implication in AMI .Aim of The Study: This study conducted to evaluate and measure level of WBC count in patient with STEMI and their effect on cardiovascular outcome.Patients and Method: we have 100 patients (male and female) with mean age (40-80) years admitted to the AL-diwaniyha teaching hospital CCU ( coronary care unit )department and peripheral blood sampling taken after 24 hrs of admission and another sample after 1 week and we record the main early and delay squally occurred. Patient that admitted to CCU were confirmed with AMI by clinical features ,examination and investigations (ECG with ST segment elevation, positive cardiac troponin) .Results: The mean WBC count in all patients was 11.260 ± 3.600 X103/ CC. There is no significant difference in mean WBC count among patients with inferior, lateral and posterior wall MI (P > 0.05); however, mean WBC count was significantly highest in patients with extensive anterolateral MI (P<0.001); followed by patients with anterior MI. Early complications were observed in 52 patients (52.0 %), these complications were in the form of arrhythmias such as VF, VT, AF, heart block and bradycardia and acute heart failure. The most common early complication was VF ( 32.0 %.)Late complications were observed in 28 patients (28.0 %), these complications were in the form of chronic heart failure or unfortunately death of patients. we noted that patient with high WBC after admission have close relation to more damage and necrotic myocyte an liable for early complications like arrhythmia (VT ,VF) and acute HF.Conclusion: WBC count remained a significant predictor of complication after admission for patients with STEMI.